The temporal and latitudinal dependences of turbulence driven by pickup ions in the outer heliosphere - Wang, Bingbing; Zhao, Lingling; Abouhamzeh, Paria; Zank, Gary P.; Adhikari, Laxman (Frontiers in Astronomy and Space Sciences, 2023)
The distribution of turbulence in the heliosphere remains a mystery, not only because of the complexity in modeling the turbulence transport equations, but in identifying the drivers of turbulence that vary with time and spatial location. Beyond the ionization cavity (a few astronomical units (AU) from the Sun), the turbulence is driven predominantly by freshly created picked ions (PUIs) in contrast to the driving by stream shear and compression. Understanding the source characteristics is necessary to refine turbulence transport models and interpret measurements of turbulence and solar wind temperature in the outer heliosphere. Using a recent latitude-dependent solar wind speed model and the ionization rate of neutral interstellar hydrogen (H), we investigate the temporal and spatial variation of the strength of low-frequency turbulence driving by PUIs from 1998 to 2020. We find that the driving rate is stronger during periods of high solar activity and at lower latitudes in the outer heliosphere. The driving rates for parallel and anti-parallel propagating (relative to the background magnetic field) slab turbulence have different spatial and latitude dependences. The calculated generation rate of turbulence by PUIs is an essential ingredient to investigate the latitude dependence of turbulence in the outer heliosphere, which is important to understand about the heating of the distant solar wind and the modulation of cosmic rays.